Fiscal Decentralization in Developing and Transition Economies: Progress, Problems, and the Promise - Shah, Anwar (World Bank, Washington, D.C., 2013)
The author discusses the revolution in public sector thinking that is transforming the public sectors of developing and transition countries. Countries are reconsidering their fiscal systems and searching for the right balance between central government control and decentralized governance. Political decentralization has advanced in most countries. Subnational expenditures in developing countries as a percentage of total public expenditures have also increased over the past two decades. However, the process is far from complete. In many countries, the central government is still involved in the delivery of local services, local governments have few sources of own-revenues, local governments have limited access to borrowing for capital projects, and the design of intergovernmental transfers does neither address regional fiscal equity nor convey appropriate incentives for fiscal discipline, improved service delivery performance, and accountability to citizens. Decentralized public governance can help realign public sector incentives through greater accountability to citizens, and attenuate the "democracy deficit" caused by globalization and the role of supranational institutions and regimes. However, this requires careful examination of the entire fiscal system. Elements of a comprehensive package of fiscal system reforms would include: (a) Clarifying roles of various levels of government in public service delivery; (b) Reassigning taxing responsibilities to ensure local revenue autonomy, accountability, and efficiency without endangering an internal common market; (c) Designing fiscal transfers to ensure regional fiscal equity and to create an enabling environment for innovative and competitive service delivery; (d) Facilitating responsible credit market access to subnational governments; (e) Designing institutional arrangements for intergovernmental fiscal relations to better coordinate policies; and (f) Aligning operational capacity with the authorizing environment through the "accountability for results" framework of public management.